Kualitas Layanan, Nilai Fungsional, Nilai Emosional, dan Kepuasan Konsumen : Sebuah Studi Kasus - Sudarso, Erik (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
The current business developments indicate that almost all of the products or services competitive to face the competition in a market. The same thing happens with existing business hotel in Singkawang city, the hotel added every year will certainly increase the amount of competition in this industry, especially in the quality of service that can fully meet the needs and desires of consumers and to give satisfaction to the consumer. The purpose of this study was to determine the effect of service quality on the functional value, influence the quality of service to the emotional value, the effect of functional value to customer satisfaction, the influence of emotional value to customer satisfaction, and the influence of service quality on customer satisfaction.